2009
DOI: 10.1007/s00011-009-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo visualization of nitric oxide and interactions among platelets, leukocytes, and endothelium following hemorrhagic shock and reperfusion

Abstract: Mesenteric endothelial cell dysfunction after H/R 0.5 h is associated with reduced NO, whereas after H/R 24 h is related to increase NO in mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…A DAF study of hemorrhagic shock (blood pressure reduced to 40 mm Hg for 20 min) in rat mesentery reports that venular endothelial NO production is reduced significantly within 30 min after restoring blood volume, with no difference from controls after 24 hr of recovery. 120 An increase in NO production in mast cells was observed after 24 hr, which could be attributed to NO production from iNOS. However, it is not possible to determine absolute NO levels in the microcirculation from any of these in vivo DAF studies.…”
Section: Soluble Guanylate Cyclase As Primary Target Of Nitric Omentioning
confidence: 94%
“…A DAF study of hemorrhagic shock (blood pressure reduced to 40 mm Hg for 20 min) in rat mesentery reports that venular endothelial NO production is reduced significantly within 30 min after restoring blood volume, with no difference from controls after 24 hr of recovery. 120 An increase in NO production in mast cells was observed after 24 hr, which could be attributed to NO production from iNOS. However, it is not possible to determine absolute NO levels in the microcirculation from any of these in vivo DAF studies.…”
Section: Soluble Guanylate Cyclase As Primary Target Of Nitric Omentioning
confidence: 94%
“…It has been shown that low NO bioavailability or NO inhibition can induce the expression of eCAMs [19-21], platelet activation and adhesion to endothelial cells [22,23] and increase baseline leukocyte rolling and adherence [24,25], and administration of NO donors inhibits endothelial activation [26]. Low NO bioavailability is a major player in vascular inflammation commonly observed in hemolytic syndromes such as sickle cell crisis, in which acellular hemoglobin acts as a strong NO scavenger [27].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Certain studies have provided evidence that cell barrier dysfunction and vascular hyperpermeability can be caused by an I/R injury via a local inflammatory response, resulting in vascular protein leakage. Glomerular barrier dysfunction and proteinuria have also been observed in the kidneys of patients with systemic I/R injuries [13][18], [23]. Hiratsuka et al reported that these responses could be observed via microscopy within 30 min of an I/R injury in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hiratsuka et al reported that these responses could be observed via microscopy within 30 min of an I/R injury in rats. [18] We therefore suspected that proteinuria may be the initial clinical presentation of a post-resuscitative I/R injury. Proteinuria would present much earlier than myocardial dysfunction, which has been reported to occur at a median time of 6.8 h following OHCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation